Pengembangan Modul Sirah Rasul Ulul ‘Azmi Untuk Meningkatkan Sikap Religius Siswa - Fitriah, Himmatul; Sinaga, Ali Imran; Anas, Nirwana (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This article aims to find out how the development of the Apostle Ulul 'Azmi sirah module in improving the religious attitude of students at SMA An-Nadwa Binjai. This study uses a 4-D model; namely definition, design, development, and deployment. Sampling used a random sampling technique with class XI A as the control class and class XI as the experimental class with a total of 35 students. The results of this study state that the feasibility of the Sirah Rasulullah Ulul 'Azmi module is feasible to use through 3 expert validation tests, the feasibility of the module is seen from 3 components namely material experts, language and design. The validation results of the three validators are: the average score of the content component is 77.27, the linguistic component is 83.65, and the presentation component is 81.73. These three scores indicate a good/proper category, which means that the Sirah Rasulullah Ulul 'Azmi module can be used with a little revision. As for the effectiveness of the Sirah Rasul Ulul 'Azmi module in increasing students' religious attitudes when seen from the test results between the control class and the experimental class, with the control class's average score of 69.71, while the experimental class's average score was 75.52. Based on the results of data analysis, it can be concluded that the Sirah Rasulullah Ulul 'Azmi module is effective in increasing religious attitudes in class XI SMA An-Nadwa in PAI learning.